Motor training‐related brain reorganization in patients with cerebellar degeneration. Issue 5 (11th December 2021) - Draganova, Rossitza; Konietschke, Frank; Steiner, Katharina M.; Elangovan, Naveen; Gümüs, Meltem; Göricke, Sophia M.; Ernst, Thomas M.; Deistung, Andreas; van Eimeren, Thilo; Konczak, Jürgen; Timmann, Dagmar
Abstract: Cerebellar degeneration progressively impairs motor function. Recent research showed that cerebellar patients can improve motor performance with practice, but the optimal feedback type (visual, proprioceptive, verbal) for such learning and the underlying neuroplastic changes are unknown. Here, patients with cerebellar degeneration ( N = 40) and age‐ and sex‐matched healthy controls ( N = 40) practiced single‐joint, goal‐directed forearm movements for 5 days. Cerebellar patients improved performance during visuomotor practice, but a training focusing on either proprioceptive feedback, or explicit verbal feedback and instruction did not show additional benefits. Voxel‐based morphometry revealed that after training gray matter volume (GMV) was increased prominently in the visual association cortices of controls, whereas cerebellar patients exhibited GMV increase predominantly in premotor cortex. The premotor cortex as a recipient of cerebellar efferents appears to be an important hub in compensatory remodeling following damage of the cerebro‐cerebellar motor system. Abstract : Voxel‐based morphometry analysis was used to obtain information on the neural correlates of visuomotor arm training in cerebellar degeneration. Whereas controls showed increased gray matter volumes in visual associative cortex, in cerebellar patients gray matter increased in premotor cortex. Findings suggest that the premotor cortex is at center stage for compensatory brain remodeling in patients with cerebellar degeneration, that is a motor area which has well‐known anatomical connections with the cerebellum.